The frequency of sleep-disordered breathing in children with asthma and its effects on asthma control - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2017)
Background: The presence of sleep-disordered breathing (SDB) in children with asthma may cause difficult to control asthma. Objectives: The aim of this study was to determine the frequency of SDB in children with asthma, to evaluate its effects on asthma control and to assess the risk factors associated with the presence of SDB. Methods: Parents of children who Sleep Questionnaire (PSQ) and the Childhood Asthma Control Test (C-ACT). Asthma control level was assessed according to Global Initiative for Asthma (GINA). Same ear-nose-throat (ENT) specialist evaluated all patients. A 4-point tonsil grading method and adenoid-nasopharynx ratio were used to categorize tonsil and adenoid size, respectively. Results: A total of 408 children (275 male, 67.4%) with a mean age of 8.1 +/- 3.2 years were included. Nearly 40% of asthmatic children were not-well-controlled according to GINA and 34.6% of all patients had SDB according to PSQ. Multivariate logistic regression analysis revealed that coexistence of SDB [OR: 6.62, 95% CI (4.21-10.41); p < 0.001)] and tonsillar hypertrophy [OR: 3.47; 95% CI (1.05-11.5); p < 0.041] were independent risk factors for not-well-controlled asthma in asthmatic children after other established contributors to asthma control were adjusted. Conclusions: Our study showed that SDB is a strong risk factor for not-well-controlled asthma in asthmatic children independent of other confounders. In addition, tonsillar hypertrophy may have a role in the association between SDB and not-well-controlled asthma in childhood.
Keywords: Sleep-disordered breathing; asthma; children; tonsil; adenoid; APNEA RISK; AIRWAY INFLAMMATION; CHILDHOOD ASTHMA; ADENOTONSILLECTOMY; DIAGNOSIS; OBESITY; HYPERTROPHY; ASSOCIATION; RELIABILITY; PREVALENCE